(untitled) (Research, Society and Development, 2023)
Malnutrition is a public health problem in Mozambique, where 37% of children under five suffer from chronic malnutrition and 4% from acute malnutrition. Since national independence in 1975, action plans have been implemented to reverse this situation. Objective: To analyze the progress made in the fight against malnutrition through the policies, action plans and programmes implemented in the country since independence. Methodology: Documentary study, whose main data sources consisted of Demographic and Health Survey reports, Family Budget Surveys, SMART Surveys, Integrated Classification of Food Security Stages reports, information from FAO databases, as well as other studies on the nutritional situation in the country. The WHO and UNICEF classifications were used to describe the prevalence rates of malnutrition. Results: Except for acute malnutrition, which reduced from high to low between 1997-2023, the prevalence of chronic malnutrition had no statistically significant reductions and remains very high. Factors such as food insecurity, high illiteracy rates, armed conflict in northern Mozambique, poverty, unequal distribution of basic resources between provinces, weak monitoring and evaluation systems in the action plans implemented, poor investment in agriculture, covid-19, as well as the effect of climate change, which constantly affects the country, are the main causes. Conclusion: Despite efforts, malnutrition continues not to show significant reductions, which calls for further study and improvement of policies, as well as the control of risk factors.